MiR-107-3p/Atp6v0e1 contributes to protective effects of two selenium-containing peptides,TSeMMM and SeMDPGQQ on lead-induced neurotoxicity - Yong Fang; Tianhang Huang; Jian Wu; Xieqi Luo; Fengjiao Fan; Peng Li; Jian Ding; Xinyang Sun (Food Science and Human Wellness)
Two selenium (Se)-containing peptides from Se-enriched rice, TSeMMM and SeMDPGQQ, possess neuroprotective potency against lead (Pb2+)-induced cytotoxicity. However, the crosstalk between mRNA and microRNAs (miRNA) involved in the neuroprotection mechanism remains to be elucidated. In this study, RNA-sequencing and miRNA-sequencing were used to independently identify differentially expressed mRNAs and small RNAs profi les in Pb2+-treated primary fetal rat cortical neurons and then the correlated miRNA-mRNA target pairs were obtained. It was found that 34 mRNAs related to oxidative phosphorylation could be reversed by pretreatment of TSeMMM and SeMDPGQQ. The protective effect of TSeMMM and SeMDPGQQ was mediated by upregulation of miR-107-3p, which downregulates the ATPase H+ transporting V0 subunit e1 (Atp6v0e1) mRNA level. A zebrafish model was applied to verify the relevance between the targeted mRNA and miRNA by real-time quantitative PCR. The results indicated that miR-107-3p was a potential therapeutic target to achieve neuroprotection of Se-containing peptides via stimulation of Atp6v0e1.